Structural diversity in new coordination polymers modulated by semirigid ether-linked pyridine-phthalate building block and ancillary ligands: syntheses, structures, and luminescence properties1. Issue 16 (28th April 2015) - Yang, Li-Zi; Fang, Ran; Dou, Wei; Kirillov, Alexander M.; Xu, Cai-ling; Liu, Wei-Sheng
<x xml:space="preserve">Abstract</x> A series of new 2D or 3D coordination polymers were self-assembled from a semirigid pyridine-dicarboxylate as a main building block and various N-donor coligands; their structural, topological and luminescence features are discussed.